The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1016/j.immuni.2012.08.016
|View full text |Cite
|
Sign up to set email alerts
|

CXCR3 Chemokine Receptor-Ligand Interactions in the Lymph Node Optimize CD4+ T Helper 1 Cell Differentiation

Abstract: SUMMARY Differentiation of naïve CD4+ T cells into T helper (Th) cells is a defining event in adaptive immunity. The cytokines and transcription factors that control Th cell differentiation are understood, however it is not known how this process is orchestrated within lymph nodes (LNs). Here we have shown that the CXCR3 chemokine receptor was required for optimal generation of interferon (IFN)-γ secreting Th1 cells in vivo. Using a CXCR3 ligand reporter mouse, we found that stromal cells predominately express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

25
424
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 375 publications
(467 citation statements)
references
References 41 publications
25
424
4
Order By: Relevance
“…They postulated that sustained contact of the already primed, but uncommitted, CD4 + T cells with the CXCL10-producing DCs in the paracortex of the lymph node allowed for expansion and full Th1 polarization. Indeed, a recent study proves this point (21). CXCR3 was upregulated on CD4 + T cells in DLNs during priming, prior to clonal expansion, and contributed to migration of Ag-specific CD4 + T cells from the T cell zone to the interfollicular and medullary regions, to interaction with DCs, and to Th1 differentiation.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…They postulated that sustained contact of the already primed, but uncommitted, CD4 + T cells with the CXCL10-producing DCs in the paracortex of the lymph node allowed for expansion and full Th1 polarization. Indeed, a recent study proves this point (21). CXCR3 was upregulated on CD4 + T cells in DLNs during priming, prior to clonal expansion, and contributed to migration of Ag-specific CD4 + T cells from the T cell zone to the interfollicular and medullary regions, to interaction with DCs, and to Th1 differentiation.…”
Section: Discussionmentioning
confidence: 80%
“…The resulting cluster formation between the primed CD4 + T cells and the DCs promoted Th1-type effector differentiation (20). A recent report corroborated and further clarified the mechanism by Division of Immunology, The Netherlands Cancer Institute, 1066 CX Amsterdam, The Netherlands which CXCL10 contributes to Th1 polarization during priming (21).…”
mentioning
confidence: 77%
“…The CXCR3 ligands CXCL9 and CXCL10 are often associated with Th1 responses (43) and were prominent among the cytokines detected in the dLN. The expression of both chemokines by LN stromal cells and DCs may have enhanced Th1 responses by creating a favorable environment facilitating T cell priming at the periphery of the dLN (44).…”
Section: Discussionmentioning
confidence: 99%
“…The additional release of CXCL10 would further increase recruitment of T cells to the local area. A recently published study demonstrated that CXCL10 production by DC is important in DC–T cell interactions during priming of T cells in the lymph node 24. It is possible that CXCL10 production by APCs is similarly important for reactivation and further recruitment of memory T cells in the brain in PND, and that CXCL10 production by responding T cells augments the response.…”
Section: Discussionmentioning
confidence: 99%
“…CXCL10 and the CXCR3 receptor have been proposed to work in an inflammation‐promoting loop in allergy27 and to modulate IFNγ production in EAE 28. CXCR3 has been suggested not only to play a role in T cell priming in the lymph node24 but also in the recruitment of T cells into peripheral target tissues 29. Taken together, these data suggest that the high concentration of CXCL10 present in PND patient CSF may be due to production of this chemokine by infiltrating autoimmune T cells interacting with APCs in the CNS 30.…”
Section: Discussionmentioning
confidence: 99%